Time-varying harmonic analysis in electric power systems with wind farms, through the possibility theory (2015)
This paper focuses on the analysis of the connection of wind farms to the electric power system and their impact on the harmonic load-flow. A possibilistic harmonic load-flow methodology, previously developed by the authors, allows for modeling uncertainties related to linear and nonlinear load variations. On the other hand, it is well known that some types of wind turbines also produce harmonics, in fact, time-varying harmonics. The purpose of this paper is to present an improvement of the former method, in order to include the uncertainties due to the wind speed variations as an input related with power generated by the turbines. Simulations to test the proposal are performed in the IEEE 14-bus standard test system for harmonic analysis, but replacing the generator, at bus two, by a wind farm composed by ten FPC type wind turbines.